O Estágio Supervisionado e o desenvolvimento profissional em Educação Física na UFAM/Manaus: concepções entre o pensado no PPC e o vivido pelos licenciandos - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
The present dissertation presents a reflection about Professional Development in the Amazon context, of Physical Education graduates from the supervised curricular internship carried out in state schools, in the city of Manaus. The general objective of this study was to understand how the curricular internship model, recommended in the Pedagogical Course Project (PPC) of Physical Education, undergraduate, from the Federal University of Amazonas, campus Manaus, has contributed to professional development, aiming to meet the needs of current demands of society. To carry out this research, we also seek to reflect on the historical and educational processes of the Physical Education course and the curricular internship in Brazil; to identify, in the Pedagogical Course Project (PPC) of a degree in Physical Education at the Federal University of Amazonas (UFAM), the training profile, the competences, the skills, the supervised internship conceptions and their objectives; to identify the students- teachers' conceptions about the importance of the supervised internship for professional development. It is a research whose approach is qualitative (MINAYO, 1994; LÜDKE; ANDRÉ, 1986), whose results will be expressed with the deepening of the phenomena from the perspective of the research subjects (BOGDAN and BIKLEN, 1994), of the study type case study (ANDRÉ, 2013), in which, in the theoretical basis, we privilege contextualized references to the Physical Education course and the role of the internship in the process of professional training and development, such as Caparroz (2007), Castellani Filho (1988, 1991) ; Darido (2003), Taffarel (1993); (Silva (2007); Lima (2012); Pimenta (2009, 2012); Ghedin (2008, 2015); Freitas (1996); García (1999, 2009), and the decree-laws of the Physical Education course and supervised internship , in addition to the DCNs for teacher training courses and the specific DCNs for the Physical Education training course. As procedures for data collection, questionnaires and semi-structured interviews were used. During the development of the work, the aim was to highlight the internship as a theoretical and practical activity that brings the licensee closer to the educational reality, and collaborates in the professional development regarding the understanding and analysis of their professional insertion space when proceeding in a critical, transforming way and creative. The results show that the researched course places its formative perspective centered on the hegemony of the instrumentalizing perspective of the technique, which limits professional development. They also point out that supervised internship takes on a peripheral character, being the practical part at the end of the training course, going against what the DCNs establish: that the curricula have the training and theoretical-practical activities diluted in the trajectory of the initial training, thus minimizing the shock with reality. Most of the interviewed undergraduates demonstrated that they did not know the PPC of the course, which is essential to clarify the desired professional profile. It was found, therefore, from the perspective of the interviewees, that the supervised internship carried out in the last period of the course does not allow a theoretical-practical articulation between the scientific knowledge arranged in the training institution with the field of activity. It is pertinent to reorganize the curricular design, establishing the curricular component of the supervised internship as an articulating axis of the initial training, allowing future Physical Education teachers to get closer to their professional practice, in order to produce and mobilize the knowledge inherent to the Full Professional Development.
Keywords: Programas de estágio; Estudante de Educação física; Projeto Pedagógico do Curso; Desenvolvimento Profissional; Educação física - Prática profissional; CIÊNCIAS HUMANAS: EDUCAÇÃO; Estágio Curricular Supervisionado; Desenvolvimento Profissional; Educação Física; PPC; UFAM